Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
One solution (9,-3)
Step-by-step explanation:
-x - y = -6
2x + 7y = -3
7(-x - y = -6) = -7x - 7y = -42
2x + 7y = -3
-7x - 7y = -42
2x + 7y = -3
-5x = -45
/-5 /-5
x = 9
-x - y = -6
-9 - y = -6
+9 +9
-y = 3
/-1 /-1
y = -3
(x, y) -> (9, -3)
Hope this helps!
![View image Esther](https://us-static.z-dn.net/files/d4d/c23491eab08afd1a4785e25d886ca365.png)
Answer:
x = 9
y = -3
Step-by-step explanation:
-x - y = -6
2x + 7y = -3
----------------------------
2(-x - y = -6)
-2x - 2y = -12
----------------------------
-2x - 2y = -12
2x + 7y = -3
5y = -15
÷5 ÷5
y = -3
----------------------------
-x - y = -6
-x - (-3) = -6
-x + 3 = -6
-3 -3
-x = -9
÷-1 ÷-1
x = 9
I hope this helps!
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.